(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Corruption in the private sector constitutes one of the mayor problems needed of regulation in the criminal Spanish legal system. Both, the international duties assumed by Spain and the inadequacy of the existing legal instruments pressures the Spanish legislator on the direction of creating a new specific category of offense that tackles the issue. Nevertheless, the 2006 amendment proposal of linking unfair competition to the breach of does not seem appropriate as it introduces an element –the breach of the agent’s duties- which, in numerous occasions, it is going to be extremely difficult toverify. Thereby, it is advisable to restrict private fiduciary dut corruption strictly tounfair competition and relegate the breach of duties to the verification of whether itexists or not an underlying unfair administration offence.